2016
DOI: 10.7458/spp2017837629
|View full text |Cite
|
Sign up to set email alerts
|

Paisagem, tecnologia e desenvolvimento local: a central solar da Amareleja

Abstract: Resumo No estudo dos impactos locais das energias renováveis tem sido dada pouca atenção a tecnologias com menor peso no sistema energético. Este trabalho procura colmatar esta lacuna, através de um estudo de caso sobre a central fotovoltaica da Amareleja, assente em entrevistas com stakeholders e residentes e análise de documentação. A central tem a particularidade de ser parte de uma iniciativa municipal de desenvolvimento regional assente nas energias renováveis. Contudo, apesar de um processo de implantaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Part of the funds generated were earmarked for local development and allocated to a social fund that supported various projects. One was an incentive scheme for domestic rooftop solar energy generation; its funds were exhausted through local demand, and it motivated other Moura residents to seek support to install solar panels (Junqueira, Delicado, and Truninger 2017). Another was a technology park, which took the shape of a solar panel quality testing laboratory (Lógica EM) that was closed in 2019 after failing to turn a profit for several years.…”
Section: The Amareleja Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the funds generated were earmarked for local development and allocated to a social fund that supported various projects. One was an incentive scheme for domestic rooftop solar energy generation; its funds were exhausted through local demand, and it motivated other Moura residents to seek support to install solar panels (Junqueira, Delicado, and Truninger 2017). Another was a technology park, which took the shape of a solar panel quality testing laboratory (Lógica EM) that was closed in 2019 after failing to turn a profit for several years.…”
Section: The Amareleja Case Studymentioning
confidence: 99%
“…While municipal representatives consider the creation of skilled jobs and the improvement of the quality of life of the local population to be major assets resulting from solar PV plants, the erstwhile mayor of the Amareleja Parish Council and the vast majority of its residents consider these effects to be rather modest (Delicado, Figueiredo, and Silva 2016). In fact, today, as in 2013-2014 (Delicado et al 2015;Junqueira, Delicado, and Truninger 2017), our online survey in Amareleja revealed a widespread idea that the PV power plant has brought few benefits to the village and its inhabitants. Respondents stated that they hold this view on the grounds that the development has created very few permanent jobs at the local level (15 earlier on, reduced to less than six by 2019); has not led to a decline in electricity prices for residents; did not promote the development of other economic activities such as tourism; and did not stop out-migration and desertification.…”
Section: The Amareleja Case Studymentioning
confidence: 99%